A magnetic field effects on redox potential of reduction and oxidation agents - Božič, Mojca (Array, 2008)
Summary: Redox potentials of two reducing (sodium dithionite and glucose) and two oxidizing (hydrogen peroxide and sodium hypochlorite) agents were monitored at various concentrations and at different temperatures for 30–75 minutes after the exposure of their water solutions (glucose and hypochlorite solutions once; sodium dithionite and hydrogen peroxide solutions one, two and/or three-times) to the static magnetic field of flux density of 0.9 V s m–2. The aim of the investigation was to suggest improvements, i.e., intensification and stability, of the reduction-oxidation ability of selected agents applicable in textile fibre processing, primarily bleaching and vat dyeing. Results of the experiments show that magnetic treatment (of solutions) raises both the reducing ability of glucose and the oxidation ability of hydrogen peroxide and sodium hypochlorite, promising some technological and economical benefits for the textile industry as well as for other fields of chemistry